Swarm intelligence-based differential protection scheme for wind integrated transmission system. (September 2020) - Prasad, Ch.D.; Biswal, Monalisa
Abstract: Conventional differential protection scheme considers a fixed threshold to detect the fault in a transmission system. In a wind integrated transmission system, any fixed threshold-based protection function is not reliable always due to the dynamic variation of control parameters of the wind turbine. To mitigate this issue, an adaptive differential protection scheme is proposed in this work for the transmission system integrated with wind farm. The method uses a particle swarm optimization (PSO) algorithm to generate an optimum threshold for the system considering the varying system and fault operating conditions. An objective function is designed for PSO considering the fault location, inception angle, and fault resistance. The method is tested by using a standard wind integrated transmission system model, simulated using MATLAB software. Performance of the method is tested for numerous test cases considering the wide variations in fault and system operating conditions.